PENGARUH EFEKTIFITAS PENGGUNAAN SOSIAL MEDIA, MODAL, DAN LAMA USAHA TERHADAP PENDAPATAN (STUDI KASUS DURIAN PJ SAMPANG): (Studi Kasus Durian Pj Sampang) - Laily Nur Aini; Septian Eko Haryansyah; Zulviar Anas (STKIP MAJENANG, 2024)
Effect of Effectiveness The use of social media, capital and length of business to increase income is nothing new for business actors. However, many micro-scale culinary entrepreneurs are still hesitant to use social media to develop their business. There are also many of them who have used social media, but have not experienced progress in their business. This research discusses the effectiveness of the use of social media, capital and length of business to increase income carried out by Durian PJ. From the problems above, this research aims to find out how effective the use of social media is for business and capital on Durian PJ Business income. This research focuses on the durian business in Sampang. This research uses E-analysis with the help of Views 8 software. The results of this research show that social media variables and length of business have a positive and significant effect on income, while capital variables have no effect on Durian PJ's business income.